THE BATTLE OF SANTIAGO. CHRONICLE OF A QUARANTINE IN THE CAPITAL OF CHILE - Azócar Guzmán, Pedro (2021)
The covid-19 pandemic hit Chile in the middle of a political and social crisis marked by clashes between citizens and institutions, accompanied by a profound critique of the economic model installed by the Augusto Pinochet dictatorship, the institutional foundation of which is the 1980 Constitution. Sebastián Piñera’s rightwing  administration tried to reap political gain from the pandemic, using it to reassert itself in power, but the health emergency revealed even more starkly the profound social inequalities that persist in the country 30 years after the return to democracy. Thus, Chile has suffered a double blow: on one hand, it faces a profound social fracture, and on the other, the coronavirus disaster. It is in this complex scenario that Chileans must vote in a plebiscite to decidewhether or not to convene a constitutional convention to bury Pinochet’s Constitution for good. This article is an approach to that scenario.